Tribands of subtrioids - Zhuchok, A.V. (Труды Института прикладной математики и механики, 2010)
We introduce the notion of a triband of subtrioids and prove that every trioid with a commutative periodic semigroup is a semilattice of unipotent subtrioids. Also we give examples of trioids which are decomposed into a triband of subtrioids.